More public and less experts : a normative framework for re-connecting the civic work of journalists with the civic work of citizens - Oelofsen, Heiletha (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2010.